Proof of concept of a sexual health outreach program led by community health workers in homeless hostels in the greater Paris region - Vaugoyeau, Emma; Rambliere, Lison; David, Manon; Lemguarni, Hanaa; Le Gac, Sylvie; Pasquet-Cadre, Armelle; Rasli, Samy; Ghosn, Jade; Rozenbaum, Willy; Bouvet, Elisabeth; Prioux, Maëlle (Frontiers in Public Health, 2024)
Context Homeless individuals face exacerbated risks of infectious diseases, including sexually transmitted infections (STIs). Programs led by Community Health Workers (CHWs) have demonstrated potential to enhance healthcare access for marginalized groups such as homeless families. This study aims to evaluate the feasibility and effectiveness of a novel CHW-based outreach program addressing sexual health issues among individuals residing in homeless hostels. Methods Twelve social homeless hostels in the greater Paris region were selected as program implementation sites. An outreach program was developed consisting of two interventions: sexual health workshops and STI screening sessions (HIV and hepatitis B and C) accompanied by individual interviews, both conducted by CHWs within each hostel over an 8-week period and scheduled weekly. Feasibility, participation and engagement were evaluated using complementary methods including qualitative field observations, semi-structured interviews and focus groups with CHWs, satisfaction questionnaires for participants, and quantitative outcome data collection of each intervention. Results A total of 80 program activities (workshops and screening sessions) were conducted. Among the participants, 542 women and 30 men engaged in workshops. During the 30 Rapid Diagnostic Testing sessions, 150 individuals underwent testing for HIV, hepatitis B, and/or hepatitis C. Positivity rates were 6.7% for hepatitis B and 0.9% for hepatitis C. No HIV infections were detected. Participant satisfaction rates were consistently high (>76%) across workshops. Qualitative analysis unveiled two critical axes influencing program feasibility and effectiveness: program organization and CHW involvement. Discussion This assessment of the program highlights its feasibility among a population that is difficult to reach through conventional healthcare efforts. The intervention’s potential effectiveness is suggested by self- and CHW-reported improvements in sexual health literacy and high rates of referral to the healthcare system, as well as holistic well-being considerations. CHW involvement is a vital determinant of program success, as are robust coordination among stakeholders, deep understanding of the target population, and strong partner engagement. Conclusion This outreach program amplifies the voices of often-overlooked populations while empowering them to navigate health and social challenges. Although these workshops serve as lifelines for those frequently excluded from mainstream services, long-term improvements to the health and wellbeing of homeless populations will necessitate systemic governmental intervention.